(untitled) (Revista Internacional de Folkcomunicação, 2022)
This article discusses the topic of popular cultures both from the notions of folkcommunication and communication in the context of social movements. The objective is to observe the presence of elements of Folkcommunication within the scope of Popular, Community and Alternative Communication developed by social movements. The study is based on bibliographic research. We conclude that popular communication within the scope of social movements carries elements of popular cultures, including folkcommunication, and, as such, mixes this expressiveness in its social practices, such as in basic education work aimed at increasing citizen awareness and in public demonstrations of protest in the exercise of citizenship.